PENGARUH LAYANAN DIGITAL PERBANKAN TERHADAP PROFITABILITAS BANK UMUM DI INDONESIA TAHUN 2017-2022 - Putri, Aisya Sylvana; Demi Pangestuti, Irene Rini (Diponegoro Journal of Management, 2024)
ABSTRACT The development of the digital world has permeated every aspect of life, where almost every aspect of human life is affected by the digitization. Digitization has revolutionized nearly all aspects of societal life, including the banking sector. Digital transformation in the banking sector has significantly altered financial services. The purpose of this research is to determine the influence of digital banking transaction intensity, digital banking transaction value, NonPerforming Loans (NPL), and diversification as independent variables on bank’s profitability measured by Return on Assets (ROA) as the dependent variable. The population in this research consists of commercial banks in Indonesia registered with the Otoritas Jasa Keuangan (OJK) and Bank Indonesia (BI) until 2022. The sample was taken using secondary data with a time series approach, in monthly data from 2017 to 2022, obtained from the OJK and BI’s publication report. Data analysis utilized the multiple linear regression test conducted using SPSS version 25. The results of this research indicate that the intensity of digital banking transactions significantly and positively effected profitability, measured by ROA (Return on Assets), while the value of digital banking transactions significantly and negatively affected ROA. Other findings from this research shows that Non-Performing Loans (NPL) have a significant and negative impact on ROA, and diversification has a positive but not significant effect on ROA.